2022
DOI: 10.1021/acsomega.2c02863
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanofibrous Scaffolds of Polycaprolactone/Gelatin Reinforced with Layered Double Hydroxide Nanoclay for Nerve Tissue Engineering Applications

Abstract: Nerve tissue engineering (NTE) is an effective approach for repairing damaged nerve tissue. In this regard, nanoparticle-incorporated electrospun scaffolds have aroused a great deal of interest in NTE applications. In this study, layered double hydroxide (LDH)-incorporated polycaprolactone (PCL)/gelatin (Gel) nanofibrous scaffolds were fabricated by an electrospinning technique. The physicochemical, mechanical, and biological properties of the scaffolds were examined. Also, the phase identification, morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…[224] Additionally, a recent study has demonstrated the potential of LDHs in nerve tissue engineering through the use of electrospinning technology to fabricate PCL/gel/LDH nanofiber scaffolds. [225] Recent developments in materials science have led to the creation of novel bone repair materials that exhibit unprecedented osteogenic differentiation performance. Among these materials are magnesium-based LDH nanosheets, which have been shown to promote osteogenesis in vitro and in vivo.…”
Section: Ldhs For Tissue Engineeringmentioning
confidence: 99%
“…[224] Additionally, a recent study has demonstrated the potential of LDHs in nerve tissue engineering through the use of electrospinning technology to fabricate PCL/gel/LDH nanofiber scaffolds. [225] Recent developments in materials science have led to the creation of novel bone repair materials that exhibit unprecedented osteogenic differentiation performance. Among these materials are magnesium-based LDH nanosheets, which have been shown to promote osteogenesis in vitro and in vivo.…”
Section: Ldhs For Tissue Engineeringmentioning
confidence: 99%
“…Having this in mind, the scaffolds showed biocompatibility with cultured SCs and supported sensory neurite outgrowth [104]. When layered double hydroxides (LDH) nanoclay particles were incorporated into electrospun PCL/gelatin, increased viability, and proliferation of the cultured human neuroblastoma SH-SY5Y cells were observed at higher LDHs, but there was no increased differentiation [105]. Photocrosslinked gelatin methacryloyl was used for the fabrication of an aligned hydrogel electrospun microfiber bundle to be used in the repair of spinal cord injury (SCI).…”
Section: Peripheral Nerve and Spinal Cord Injurymentioning
confidence: 99%
“…Polycaprolactone is less hydrophilic than poly-lactide acid and, as such, shows less cell adhesion, thus it is often crosslinked with other polymers or bioactive agents. Polycaprolactone has been used in combination with natural polymers, such as collagen or synthetic materials such as polyvinyl alcohol, to form a nanofibrous scaffold loaded with a bioactive agent for skin regeneration purposes and promotion of diabetic wound healing [ 30 , 48 , 51 , 69 , 70 ].…”
Section: Polymers Used In the Fabrication Of Nanofibrous Scaffoldsmentioning
confidence: 99%
“…It produces optimally porous and flexible scaffolds with excellent moisture-absorbing characteristics, enhanced oxygen exchange qualities, and a level of antibacterial effect [ 72 ]. It can be applied in numerous fields, but it has gained popularity in the medical field specifically due to its benefits in the formulation of nanofibrous scaffolds used in skin regeneration, wound healing, and drug delivery systems [ 69 , 76 ].…”
Section: Commonly Employed Manufacturing Techniquesmentioning
confidence: 99%